العقد النضيد على نكتة التوحيد للشيخ عمرو بن رمضان الجربي التلاَتي (متوفى 1187ه) - معطاالله, جمال (جامعة الدول العربية, 2012)
Keywords: Foi -- Traité -- 17e siècle

القواعد الأصولية و أثرها على اختلاف الفقهاء تطبيقاً على كتاب النكاح - باشعيب, وليد صالح (جامعة أم درمان الاسلامية, 2012)
Keywords: Fiqh -- mariage

جوابات الشيخ أبي نبهان الخروصي في العقيدة من خلال كتاب قاموس الشريعة - السيابي, عبد الله بن حميد (كلية العلوم الشرعية, 2012)

الإمامة والصراع على السلطة فى عمان أواخر دولة اليعاربة ( 1131 هـ / 1719 م - 1162 هـ / 1749 م ) : دراسة فى التاريخ السياسى - المسكرى, سيف بن عدى بن سلطان (جامعة السلطان قابوس, 2012)
Keywords: Vie politique -- Oman -- 18e siècle

المؤسسة التنصيرية في الصحراء الجزائرية في نهاية القرن 19م مزاب والأهقار نمزذجا - حاج ابراهيم, امحمد (جامعة قسنطينة 2, 2012)

دور الحركة التجارية في ازدهار قصور إقليم توات ووادي ميزاب وتطورها خلال العصور الحديثة 10هـ الى 13هـ / 16-19م - علال, ليندة (المدرسة الوطنية المتعددة التقنيات للهندسة المعمارية, 2012)

الشيخ أبو إسحاق إبراهيم اطفيش وقضايا المشرق العربي في مجلة المنهاج 1925/1931م - شعشوع, معمر بن العربي (جامعة الجزائر 2, 2012)
Keywords: Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965)

المجتمع المدني والإعلام البيئي في الجزائر: الجمعيات البيئية في مدينة غرداية نموذجا - قشار, بكير بن بايوب (جامعة الجزائر 3, 2012)

المقاصد الشرعية في احكام الشهادة - ويرو, سعيد بن يحيى (جامعة الجزائر, 2012)

معلم الفكر الإصلاحي عند الشيخ بيوض وتطبيقه في المجتمع - ابن صالح, مصطفى بن داود (جامعة الجزائر, 2012)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Réformisme -- Mzab

‎⁨الجنوب الشرقي الجزائري خلال العهد الإستعماري ورقلة انموذجا⁩ - شافو, رضوان (جامعة الجزائر 2, 2012)
Keywords: Ouargla -- Histoire

‎⁨الجملة الفعلية وأنماطها في إلياذة الجزائر للشاعر مفدي زكرياء دراسة دلالية - حامدي, محمد العروسي (جامعة الجزائر 2, 2012)

Restructuration du centre ancien de la ville de Midoun - Hamroun, Ramzi; Khemakhem, Mohamed (Ecole nationale d'architecture et d'urbanisme, 2012)
Keywords: Architecture -- Djerba

استراتيجية الوزن والإيقاع في إلياذة الجزائر لمفدي زكرياء - نباني, الناصر (جامعة عمار ثليجي, 2012)

‏التعليم الجماعي و القيام السوسيودينية للفتاة المزابية - فخار, إبراهيم (المركز الجامعي بغرداية, 2012)
Keywords: Enseignement -- Mzab

Réhabilitation du Patrimoine Ksourien à Travers La Revitalisation de l’Habitat. Cas des ksour de la wilaya de Ouargla - Hafsi, Mustapha (Ecole Polytechnique d'Architecture et d'Urbanisme, 2012)
Keywords: Architecture -- Ouargla

Political Development and its Role in the Stability of the Sultanate of Oman (1981 - 2012) = التنمية السياسية ودورها في الاستقرار السياسي في سلطنة عمان (1981-2012) - الدرمكي, علي بن سليمان بن سعيد (جامعة الشرق الأسط, 2012)
Keywords: Vie politique -- Oman -- 1970-2020

دور منطقة غرداية في الحركة الوطنية الجزائرية 1919-1945 - بكار, الدهمة (جامعة الجزائر 2, 2012)
Keywords: Mouvement national -- Mzab

أثر البراءة على العلاقة الزوجية - مطهري, بیة بنت عبد الوهاب (كلية المنار للدراسات الإسلامية, 2012)

Un conquistador à la découverte de l'autre. Les Naufragios d'Alvar Nuñez Cabeza de Vaca - Mariani, Catherine (Université Paris 3, 2012)
Alvar Nuñez Cabeza de Vaca (1490-1557), hidalgo de la meilleure noblesse espagnole, est l’auteur d’une relation de voyage très significativement intitulée Naufragios (1542) qui constitue le coeur de cette thèse intitulée : "Un conquistador à la découverte de l’autre : Les Naufragios d’Alvar Nuñez Cabeza de Vaca". Elle vise à démontrer que le caractère exceptionnel de ce texte réside tout autant dans son contenu que dans la personne de son auteur, brutalement et bien malgré lui confronté au choc de l’altérité, du fait d’une immersion involontaire, prolongée et totale parmi différentes ethnies de l’actuel continent nord-américain. À son retour en Europe, il retranscrit dans un mémoire les différentes étapes de cette découverte et de sa prise de conscience de l’humanité pleine et entière des Indiens, cet "autre" qu’il évoque longuement après l’avoir attentivement observé. Pour Alvar Nuñez Cabeza de Vaca, les Indiens sont en tous points ses semblables, des hommes qu’il convient de traiter comme tels et dont il devient, contre toute attente, l’ardent défenseur devant la plus haute autorité temporelle et spirituelle d’Espagne, le Roi. Son texte, à la qualité littéraire inclassable, ne relate pourtant pas une aventure unique. C’est à lui cependant qu’il doit sa postérité. Considéré tour à tour comme le premier écrivain américain, un ethnologue avant l’heure ou comme le premier défenseur authentique des Indiens, Alvar Nuñez Cabeza de Vaca, à l’issue d’un périple de près de 10 ans au cours duquel il a parcouru le continent américain d’Est en Ouest connaît la déchéance sociale et n’a pas vu ses idées triompher de son vivant.
Keywords: Invasions chrétiennes -- Djerba

A Sea of Debt: Histories of Commerce and Obligation in the Indian Ocean, c. 1850-1940 - Bishara, Fahad Ahmad (Duke University, 2012)
Keywords: Commerce -- Zanzibar -- 19e siècle

حياة الحضارية في الجزائر الرستمية (م909-777/ هـ 296-260) - قرواز, فتيحة (جامعة حسيبة بن بوعلي, 2012)
Keywords: Vie intellectuelle -- Rustumides

المؤسسة التنصيرية في الصحراء الجزائرية في نهاية القرن 19م (مزاب والأهقار نموذجا) - حاج أمحمد, ابراهيم (جامعة قسنطينة 2, 2012)

الآراء العقدية لأبي الربيع سليمان بن يخلف المزاتي (ت471ه.) من خلال كتابه التحف المخزونة - بومعقل, حمزة بن بوسهال (جامعة الجزائر, 2012)

La Grande Discorde - Perras-Foisy, Jules-Valery (Université de Sherbrooke, 2012)

The Ibāḍī Traders of Bilād al-Sūdān - van Riel, J.H. (The American University in Cairo, 2012)
Keywords: Commerce transsaharien

التعارض والتريخ في المذهب الإباضي دراسة مقاربة بالمذاهب الأخرى - داودي, كريم (جامعة وهران, 2012)

العمل بالاحتياط في الفقه الإباضي، نظرة تأصيلية تطبيقية - إتبيرن, رستم بن عيسى (جامعة الجزائر, 2012)
Keywords: Fiqh

Espionage in the 16th Century Mediterranean_ Secret Diplomacy, Mediterranean Go-Betweens and the Ottoman Habsburg Rivalry - Gürkan, Emrah Safa (Georgetown University, 2012)
Keywords: Ottomans -- Djerba

Oman's maritime doctrine - Aljabri, Khamis Salim Sulaiman (University of Exeter, 2012)
The economic and security significance of maritime and political interests around the world has altered with the changing international security environment, as has the importance of secure sea routes to meet global demand. Oman increasingly relies on the sea for maritime trade and exploitation of marine resources, but without a common maritime policy and strategy to align its commercial and maritime interests, its offshore resources will remain under-developed. Oman’s primary interest is to ensure national maritime security by maintaining an effective navy and other agencies to guard its sea areas, and protect its maritime trade. However, it still lacks a formal maritime doctrine to underpin its policies This study argues that a maritime doctrine will assist Oman to utilise its maritime power and protect its national interests. In the absence of archive material, this study has drawn upon personal interviews with maritime experts and practitioners, and reviewed and analyzed a wide range of official publications and secondary sources on maritime policy and doctrine. It highlights the relationship between economic growth and maritime trade in Oman, examines the role of Oman’s shipping industry and related activities, and compares the experiences and expertise of several nations that have established maritime doctrine. Oman’s need for a maritime doctrine in order to protect its national interests and sovereignty is pressing. It should connect and coordinate its maritime power, military strategy, policies, and standing operating procedures through a single maritime doctrine that will provide the basis for mutual understanding between units of the Sultan’s Armed Forces, related government agencies, and national policy-makers, ensuring operational familiarity and efficiency. In proposing a discrete administrative body to oversee the codification of principles and procedures, the study fills a significant gap in Oman’s national maritime policy and strategy, since the expression of maritime doctrine will help protect the integrity and interests of the state and its people.
Keywords: Droit maritime -- Oman

Leadership of private universities and colleges in the Sultanate of Oman - Balushi, Ali Hamdan al- (University of Southampton, 2012)
The rapid economic and social development in the Sultanate of Oman has led to an increasing demand for higher education since 1970. The Government is now involved, and is encouraging the private sector to provide higher education services through colleges and universities in order to prepare Omanis with the qualifications and skills required to support the country`s future political economic development. Higher education in the Sultanate of Oman has a range of different challenges, such as educational policies and regulations, the management of universities and colleges, funding, and maintaining quality standards in higher education institutions. One of the major challenges facing the decision makers in higher education in Oman is the effectiveness of the leadership of colleges and universities. Strong academic leadership is paramount to the effective running of educational institutions, and a professional measurement is needed to analyse the current management of these institutions. There is the need for a proper policy to ensure the recruitment of suitable leaders to run these establishments in order to respond to the dynamic changes within the society. The public and the government want to maintain a balanced situation where the private higher education institutions are enjoying a good income while providing quality education. The research aims to analyse the type of leadership required in higher education in Oman by examining government policies and strategies related to higher education. More specifically, it will evaluate the performance of leadership at the level of presidents and deans and their roles in selected private higher education institutions. By doing so, different leadership theories, perceptions of leadership and possible measures for assessing the effectiveness of leadership will be interpreted and analysed. This research is inductive based on a qualitative and exploratory approach. The findings have contributed to the development of an academic leadership model applicable to the Oman higher education institutions, and have generated some recommendations to develop the performance of presidents and deans of higher education institutions to attain the level which is acceptable to the Government and Omani society.
Keywords: Enseignement -- Oman

Substance and Things: Dualism and Unity in the Early Islamic Cultural Field - Ali, Ghazoan (University of Exeter, 2012)
The purpose of this study is to sample a number of disparate texts from the early Islamic cultural field to explore the shared grounds or themes that bind them together. The focus of the sampled texts and their analysis is the different relations between God and the real things of this world. The method that is applied in the selection of the texts of this research relies on Pierre Bourdieu’s approach to the study of cultural production. It assumes a relational and dynamic intellectual field which creates interlinked differences and similarities. This is the reason for sampling texts which are assumed to be reasonably marginal to the main cultural establishment. The kalām of the early stage, exemplified by the texts of the Zaydī al-Qāsim al-Rassī and the eastern Ibādīs, is found to emphasise the radical separation between the creator and the created. The development of this relation, which is explored through an intertextual reading of Qurʾānic exegesis, bridges the fissure, between creator and created, through the process of re-interpreting the terms of creation. The act of creation itself becomes an act of transformation, and the objects of creation become eternal ‘non-existent things’ that acquire the quality of existence. In the philosophical works of Jābir Ibn Ḥayyān, the things of this world are also reduced to transformations within the one substance that encompasses the intelligible and the material world. The results of this research show that there is a great degree of diffusion of ideas in this early stage of Islamic culture, from an assumed centre to the margins, and vice versa. The general tendencies in the texts considered reflect, on the one hand, a critique of multiplicity of principles, particularly dualism, and an emphasis on God’s unity, through different interpretations of tawḥīd. On the other hand, the sought unity itself established God’s radical transcendence from the real world, thus leading to another form of dualism dividing the world and the absolute other. The process of opposition to dualism seems to have eventually produced two forms of affirming and defining unity. Both forms define the existent things in terms of substance (jawhar), however, the kalām model expresses it in atomistic terms whilst the alchemical model of Jābir expresses it in terms of a hylomorphic model. One of these redefines the meanings of the existent and the non-existent things in term of subsistence, and the other, develops the idea of a single substance with different gradation in being.
Keywords: Philosophie islamique

La théologie ibâdite omanaise du 1er / 7e au 7e / 13e siècle - Ismāʿīlī, Aḥmad (École pratique des hautes études, 2012)
Cette thèse renvoie à la fondation politico-théologique du mouvement kharijite aux premiers siècles de l’islam. L’école ibadite est l’un des mouvements kharijites qui représentent l’opposition politique à l’islam classique au premier siècle. Cette étude ne présente pas uniquement la pensée théologique et les racines historiques de l’école ibadite. Elle s’est employée à observer l’instant crucial de l’histoire où le texte sacré a commencé à imprégner la vie quotidienne, menant ensuite aux multiples visages de l’islam, ce que l’on nomme aujourd’hui l’islam pratique, l’islam politique, l’islam théologique, l’islam juridique, etc. Cette thèse a essaye de faire analyser des questions théologiques qui sont dépendantes de deux contextes distincts : 1. Un contexte philosophique qui concerne toute question philosophique empruntée à la culture préislamique, telle la théorie de l’atome. D’autres encore, davantage métaphysiques, comme la théorie de l’essence divine et ses attributs ; la théorie de l’acte humain, etc. Ces problématiques sont apparues chronologiquement au cours du 2e/VIIIe siècle. 2. Un contexte épistémologique lié au cadre sociopolitique dans lequel évolue la communauté musulmane. Sa compréhension permet d’appréhender les hiérarchies religieuses de l’être humain, autrement dit l’application des hiérarchies de la divinité à l’être humain (croyant parfois et mécréant quelquefois, pieux ou hypocrite, etc.). Cette thèse a essayé autant que possible de suivre les étapes historiques et théologiques parcourues par l’école ibadite du 1er/7e au 7e/13e siècle. Cette école est considérée comme une extension historique et politique des mouvements kharijites en général, et ce sont ces derniers qui incarnent l’opposition politique en islam, qui ont ensuite soulevé les questions théologiques liées aux termes coraniques. Studying the history of the Ibadhi school and its creed represents a crucial element in academic studies. The present study is not just one of the few academic dissertations that worked to analyze the history and theology of Ibadism thought, but also belongs to an important field about the political Islamic foundation in the early centuries. That is the Khawariji (outsiders) thought which is an important part of the opposition in the political Islam, as well as Shiite ideology in general. This dissertation attempted somewhat to cover all the historical periods of Ibadhi theological school. This school is a political, historical, and theological extension of Kawarij who founded the political Islam in the 1st century and were active in establishing the conceptual principles for theological Islam through provoking the issues about the reality of the believer, hypocrite, disobeyer, etc. 1. This dissertation studied the development of concepts, their theological connotations, and their link to the social political situation in which they were generated and developed. Then, it analyzed the theological issues related to such concepts. 2. This study observed the change of Ibadhism from being a political movement to the foundation of a theological school that could establish an independent state in Oman. 3. An attempt to document the thematic development of theological issues in Ibadhism from the 1st century to the 7th century, and study their theological concepts and connotations, and their link to the social political situation of theology in Ibadhism. 4. This study conducted thematic and time comparison with the Ash’ari and Muatazela schools though considering the development of the related theological concepts and connotations from the 1st to the 7th century. 5. This study is restricted to the most prominent theological issues which actually lead to the foundation of theology, such as the issues of atom, divine entity, action of humans, vision, creation of the Quran. These are the issues that are major in theology and distinguish theological schools.

الخلاف الفقهي بين المالكية والإباضية في كتاب العبادات : دراسة تحليلية استقرائية مقارنة فى العبادات - الكاتب, عبد المحسن سالم (جامعة القاهرة, 2012)
Keywords: Fiqh

آل الجلندى في عمان :‏ ‏دورهم منذ ما قبل الإسلام حتى منتصف القرن الثالث الهجري/ منتصف القرن التاسع الميلادي :‏ ‏دراسة تاريخية - البرطمانية, مريم بنت سعيد (جامعة السلطان قابوس, 2012)
Keywords: Vie politique -- Oman -- 749-751

متاحف الفنون والعادات الشعبية بجزيرة جربة: متحف جربة للتراث التقليدي الحوافز والحدود والافاق - الثابت, علي (المعهد العالي لمهن التراث بتونس, 2012)
Keywords: Musée -- Djerba

العمارة الإقتصادية التقليدية في جزيرة جربة: مدوٌنة المعالم الاقتصادية التقليدية - الصغير, نجيب (كلية العلوم الانسانية والاجتماعية, 2012)
Keywords: Architecture -- Djerba; Bardawi, mosquée al- (Mezrane, Djerba); Monuments -- Djerba

البطولة فى شعر الخوارج - أبو ركبة, ثائر شعبان محمد (الجامعة الإسلامية, 2012)
Keywords: Poésie kharijite

أحاديث أهل السنة التي تأولتها الفرق الإسلامية (الخوارج، الشيعة الإمامية، المعتزلة) - الشمايلة, معاذ عايد عبدالحميد (جامعة العلوم الإسلامية العالمية, 2012)
Keywords: Kharijisme

تحقيق كتاب جامع أبي مسألة تأليف الشيخ أبي العباس أحمد بن محمد بن بكر عاش في القرن الخامس الهجري ق 5 هـ - السعدي, فهد بن علي (جامعة الازهر, 2012)

Vers un Tourisme durable en Tunisie : Le cas de l’île de Djerba - Dribek, Abderraouf (Université de Bretagne Occidentale, 2012)
Keywords: Tourisme -- Djerba

Etude morphologique physiologique et biochimique comparée de quelques cultivars d’orge (Hodeum vulgare L.) de l’ile de Djerba soumis au stress hydrique - Zarrouk, Kawthar (Faculté des Sciences de Tunis, 2012)
Keywords: Botanique -- Djerba

Les murex dans le Sud Est tunisien (Mahares, Zarzis et Jerba) - Ben Dhia, Wafa (Faculté des Sciences Humaines et Sociales, 2012)
Keywords: Archéologie -- Djerba; Murex -- Djerba